Streamlined modular synthesis of saframycin substructure via copper-catalyzed three-component assembly and gold-promoted 6-endo cyclization - Asahi Kanno; Ryo Tanifuji; Satoshi Yoshida; Sota Sato; Saori Maki-Yonekura; Kiyofumi Takaba; Jungmin Kang; Kensuke Tono; Koji Yonekura; Hiroki Oguri (Beilstein Journal of Organic Chemistry)
The integration of copper(I)-catalyzed three-component coupling with gold(I)-mediated 6-endo cyclization streamlines the rapid and modular assembly of the substructure of bis-tetrahydroisoquinoline (THIQ) alkaloids. The design of the key synthetic intermediate bearing a 2,3-diaminobenzofuran moiety allows both gold(I)-mediated regiocontrolled 6-endo hydroamination and temporary protection of nitrile and phenolic hydroxy groups. The synthetic strategy enabled the efficient synthesis of the substructure of saframycins bearing isoquinoline and THIQ units in just four steps from the modular assembly of the three components. We also found the unexpected involvement of a fluorescent intermediate in the cascade synthetic process.